The deadly business of an unregulated global stem cell industry - Lysaght, Tamra (Journal of medical ethics, 2017)
In 2016, the Office of the State Coroner of New South Wales released its report into the death of an Australian woman, Sheila Drysdale, who had died from complications of an autologous stem cell procedure at a Sydney clinic. In this report, we argue that Mrs Drysdale's death was avoidable, and it was the result of a pernicious global problem of an industry exploiting regulatory systems to sell unproven and unjustified interventions with stem cells.